(untitled) (Zamonaviy ilmiy-texnik tadqiqotlar, 2025)
In recent years, a number of reforms have been carried out in the world for the protection of medicinal plants, the prudent use of natural resources, the creation and processing of plantations where medicinal plants are grown. However, the analyzes show the need to create an additional value chain for the protection of medicinal plants, the creation of their plantations, processing, with special attention paid to the use of bioproducts in these processes.